MANAGEMENT OF LIQUID MEDICAL WASTES IN SELECTED HOSPITALS IN YOLA, ADAMAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Liquid medical waste management has been a critical challenge in healthcare facilities and poses a severe threat to public health, particularly in developing countries. As such, this study was conducted to assess the prevailing practices of managing Liquid Medical Wastes in selected Hospitals in Yola, Nigeria, to improve on the existing practices and mitigate the dangers of mishandling liquid medical waste. One hundred and eight structured questionnaires were administered to healthcare workers and waste contract staff. Visits were made to various locations to observe the entire process of liquid medical waste (LMW) generation and its ultimate disposal. The data were subjected to a t-test using SPSS version 23.0. The study revealed that the major types of LMW reported by respondents were infectious wastes, with Hospital One (H1) reporting 69% and Hospital Two (H2) reporting 78%. The least common types of LMW generated were pharmaceutical waste, with H1 at 12% and H2 at 10%. The different types of LMW generated between H1 and H2 did not exhibit any significant distinction (P > 0.05). The various techniques used in managing LMW at the selected hospitals include segregation, temporary storage, treatment, and on-site transportation. There was a significant difference between H1 and H2 in terms of the techniques used in managing LMW (P = < 0.05). The study revealed that H2 doesn’t treat their LMW before disposal as compared to H1, where LMW from the laboratories was autoclaved before being taken to the incinerator on-site for further treatment.
Keywords: Liquid Medical Wastes Management; public health; healthcare workers; infectious wastes